The Operational Strategies of a Manufacturing Company: The Case of Italmetal - Fidanza, Roberto (Strategie operacyjne przedsiębiorstwa produkcyjnego: przypadek Italmetal, 2025)
The article examines strategies to increase operational efficiency at Italmetal, a manufacturer of cold-stamped metal components for the automotive and household appliance sectors. The analysis identified key issues such as low overall equipment effectiveness (OEE), extended changeover times, and supply chain management inefficiencies. A combination of quantitative (KPI, OEE, backlog analysis) and qualitative (SWOT, benchmarking, interviews) methods was used to identify the primary sources of inefficiency. In response to the diagnosed challenges, a comprehensive improvement plan was implemented based on Lean Management, Six Sigma, Total Quality Management (TQM) and Business Process Reengineering approaches. Key actions include waste elimination, process standardisation, capacity planning, preventive maintenance and digital integration using IoT technologies and ERP systems. Particular emphasis was also placed on the development of human capital, systematic training and interdepartmental cooperation as the foundation for lasting organizational changes. The case study presents the implemented improvements in three strategic pillars: processes, human resources, and technology. The use of operational tools such as Power BI, Kanban and FIFO logistics supports real-time decision-making and contributes to increased efficiency. The results obtained indicate a significant improvement in productivity, quality and operational flexibility, allowing Italmetal to maintain its competitive advantage and ensure long-term, sustainable development.
Quote as: Fidanza, R. (2025). The Operational Strategies of a Manufacturing Company: The Case of Italmetal. In A. Witek-Crabb & J. Radomska (Eds.), New Trends in Business Management. Strategy, Branding, Teamwork (pp. 67-81). Publishing House of Wroclaw University of Economics and Business.
Keywords: lean manufacturing; operational efficiency; Ishikawa; PDCA; digitalisation; efektywność operacyjna; cyfryzacja